Determinants of Academic Fraudulent Behavior Using the Fraud Diamond Theory Approach - Fahmie, Arief (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Education aims to help humans to increase their potential through the field of study. Education is a process of positive character building so that a person becomes intelligent and has mental, emotional, and spiritual integrity. Education not only conveys knowledge and skills but also trains instincts, and builds habits, attitudes, and correct behavior in students. Various cases of academic fraud have made it difficult for educational institutions to achieve their goals. Fraud can occur in any field including in the academic field. This fraud is usually carried out by adults who consciously and deliberately commit fraud to obtain personal or group benefits. This study examines the effect of pressure, opportunity, rationalization, and capability on academic fraudulent behavior. The population in this study were students of the Accounting Bachelor Program at the Institute of Business and Informatics Kesatuan. The research sample was 110 respondents. This study uses primary data from a questionnaire designed using a 1-4 Likert scale. Data were analyzed using multiple linear regression. The results of the analysis show that pressure, opportunity, and rationalization have a positive effect on academic fraud behavior, while capability does not affect academic fraudulent behavior.